Faktor Determinan Sosial Risiko Post Traumatic Stress Disorder (PTSD) Pasca Kejadian Bencana Tsunami Selat Sunda - Helia Rachma; Thresya Febrianti (Jurnal Kesehatan, 2021)
The Tsunami of the Sunda Strait in December 2018 resulted in many losses, fatalities, and infrastructure. The psychological impact that often occurs during a catastrophic event is Post Traumatic Stress Disorder (PTSD) and if a teenager experiences it will have an impact on life in the future. The purpose of this study was to analyse the social determinants associated with PTSD in post-Tsunami Banten. This research is a quantitative study with a cross-sectional study design with a sample size of 125. The sampling technique uses Proportional to Size (PPS) and Simple Random Sampling. Data analysis using Fisher's Exact test. Factors related to the risk of Post Traumatic Stress Disorder (PTSD) are family support (p-value 0,042<0,05) and peer support (p-value 0,021<0,05) significantly related to the risk of Post Traumatic Stress Disorder in adolescents in SMPN 2 Labuan. However, volunteer support and support of religious leaders do not have a significant relationship with the risk of Post Traumatic Stress Disorder (PTSD). Support of family and friends are risk factors PTSD in adolescents at SMPN 2 Labuan after the Sunda Strait tsunami disaster in December 2018. There needs to be socialization related to post-disaster mental health management to parents and peers.